Aluminum alloy powder suitable for laser additive manufacturing, preparation method and application of aluminum alloy powder, laser additive manufacturing aluminum alloy and preparation method of laser additive manufacturing aluminum alloy
By adding Si, Mn and Ti elements to the Al-Cu-Mg alloy and preparing aluminum alloy powders by aerosolization method, the problem of cracks and pores in laser additive manufacturing is solved, and high-performance aluminum alloy forming is achieved.
Patent Information
- Application Number
- CN202510081980.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-22
AI Technical Summary
Aluminum alloys are prone to cracks and pores during laser additive manufacturing, resulting in failure in forming or degradation in performance.
By introducing Si, Mn and Ti elements into the Al-Cu-Mg alloy, low-melting point eutectic and metastable phases are formed, the tendency of alloy cracking is reduced, and aluminum alloy powder is prepared by aerosolization method to optimize particle size distribution to improve forming performance.
The crack-free and pore-free forming of aluminum alloy powder in laser additive manufacturing is achieved, and the crack resistance and wear resistance of the alloy is improved.
Smart Images

Figure CN119859770A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal additive manufacturing, and specifically relates to an aluminum alloy powder suitable for laser additive manufacturing, a preparation method and application thereof, and a laser additively manufactured aluminum alloy and a preparation method thereof. Background Art
[0002] Aluminum alloys have been widely used in the aerospace and transportation industries due to their low cost and high strength-to-weight ratio. For example, more than 20% of the materials used to make aircraft are aluminum alloys. With the increasing demand for lightweight structures, complex geometries, high performance and high efficiency, the demand for advanced structural components is also growing.
[0003] Laser additive manufacturing technology provides a new method for manufacturing highly complex parts. The process uses a laser beam as a heat source to produce metal parts by melting a powder bed layer by layer. It has the advantages of near-net shape, high cooling rate, and design flexibility. However, since aluminum powder has high reflectivity, high thermal conductivity, low powder density, poor fluidity, and is easy to oxidize, it faces many challenges during laser processing. Studies have shown that aluminum alloys are prone to cracks and pores when processed using selective laser melting technology. In traditional high-strength aluminum alloys such as 2000 series and 7000 series materials, these problems may lead to forming failure or performance degradation. Summary of the invention
[0004] The purpose of the present invention is to provide an aluminum alloy powder suitable for laser additive manufacturing, a preparation method and application thereof, laser additive manufacturing of aluminum alloy and a preparation method thereof. The aluminum alloy powder provided by the present invention has no bubbles and cracks when laser additive manufacturing is used, thus broadening the application of aluminum alloy.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides an aluminum alloy powder suitable for laser additive manufacturing. The aluminum alloy powder comprises, by mass percentage, 3-5% Cu, 1-3% Si, 1-2% Mg, 0.6-0.8% Ti, 1-2% Mn, and the balance Al.
[0007] Preferably, in terms of mass percentage, the aluminum alloy powder comprises 3.5-4.5% Cu, 1.5-2.5% Si, 1.2-1.8% Mg, 0.65-0.75% Ti, 1.2-1.8% Mn, and the balance Al.
[0008] Preferably, the particle size of the aluminum alloy powder is 10 to 100 μm.
[0009] The present invention also provides a method for preparing the aluminum alloy powder described in the above technical solution, wherein the aluminum alloy powder is prepared by a gas atomization method.
[0010] The present invention also provides the use of the aluminum alloy powder described in the above technical solution in laser additive manufacturing.
[0011] The present invention also provides a method for preparing aluminum alloy by laser additive manufacturing, using the aluminum alloy powder described in the above technical solution and adopting a selective laser melting process for additive manufacturing.
[0012] Preferably, the parameters of the selective laser melting process include: laser power 300-350 W, scanning speed 1000-1500 mm / s, and scanning line spacing 80-120 μm.
[0013] Preferably, the preheating temperature of the substrate during the additive manufacturing is 70-100°C.
[0014] Preferably, the layer thickness during the additive manufacturing is 20-40 μm.
[0015] The present invention also provides a laser additively manufactured aluminum alloy prepared by the preparation method described in the above technical solution, and the phase composition of the laser additively manufactured aluminum alloy includes an aluminum matrix and an intermetallic compound.
[0016] The present invention provides an aluminum alloy powder suitable for laser additive manufacturing. The aluminum alloy powder comprises, by mass percentage, 3-5% Cu, 1-3% Si, 1-2% Mg, 0.6-0.8% Ti, 1-2% Mn, and the balance Al. The present invention introduces Si, Mn, and Ti elements on the basis of Al-Cu-Mg alloy. When additive manufacturing is performed, low-melting-point eutectic can be formed under the action of Si to fill the dendrite gap, thereby reducing the tendency of alloy cracking; metastable D0 is formed under the action of Ti. 22 -Al3Ti phase can serve as an effective heterogeneous nucleation core and promote the formation of equiaxed crystals, which is beneficial to grain refinement and further improves crack resistance; at the same time, Mn is supersaturated and solid-dissolved in the aluminum matrix, which increases lattice distortion, improves work hardening ability and oxidation resistance, and makes the aluminum alloy powder suitable for laser additive manufacturing. The results of the embodiment show that the aluminum alloy powder suitable for laser additive manufacturing provided by the present invention is formed by the selective laser melting process without defects such as cracks and pores. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a SEM image of the aluminum alloy powder in Example 1 of the present invention;
[0018] Figure 2 This is a macroscopic photograph of the laser additively manufactured aluminum alloy prepared in Application Example 1 of the present invention;
[0019] Figure 3 The microstructure of the laser additively manufactured aluminum alloy prepared in Application Example 1 of the present invention, wherein (a) is a metallographic microstructure magnified 100 times, (b) is a TEM microstructure magnified 500 times, (c) is a SEM image magnified 2500 times, and (d) is a SEM image magnified 2500 times;
[0020] Figure 4 The friction coefficient variation curves of the laser additively manufactured aluminum alloy prepared in Application Example 1 of the present invention, (a) is the friction coefficient variation curve at a load of 2.1N, (b) is the friction coefficient variation curve at a load of 10N, (c) is the friction coefficient variation curve at a load of 24N, and (d) is the friction coefficient variation trend under different load conditions;
[0021] Figure 5 This is a wear rate diagram of the laser additively manufactured aluminum alloy prepared in Application Example 1 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION
[0022] The invention provides an aluminum alloy powder suitable for laser additive manufacturing. The aluminum alloy powder comprises, by mass percentage, 3-5% Cu, 1-3% Si, 1-2% Mg, 0.6-0.8% Ti, 1-2% Mn, and the balance Al.
[0023] In terms of mass percentage, the aluminum alloy powder provided by the present invention includes 3-5% Cu, preferably 3.5-4.5%; as an embodiment of the present invention, the mass percentage of Cu can be 3.2%, 3.6%, 3.7%, 4.2%, 4.6% or 4.8%. The present invention limits the mass percentage of Cu to the above range, and Cu can be combined with other alloy elements to form a nano-precipitated phase, which can improve the strength of the aluminum alloy.
[0024] In terms of mass percentage, the aluminum alloy powder provided by the present invention includes 1 to 3% Si, preferably 1.5 to 2.5%; as an embodiment of the present invention, the mass percentage of Si can be 1.2%, 1.6%, 1.7%, 2.2%, 2.6% or 2.8%. The present invention limits the mass percentage of Si to the above range. During additive manufacturing, a low melting point eutectic can be formed under the action of Si to fill the gaps between dendrites, thereby reducing the risk of cracking of the aluminum alloy; and Si can form intermetallic compounds with other alloying elements, which is beneficial to improving the wear resistance of the aluminum alloy.
[0025] In terms of mass percentage, the aluminum alloy powder provided by the present invention includes Mg 1-2%, preferably 1.2-1.8%; as an embodiment of the present invention, the mass percentage of Mg can be 1.1%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7% or 1.9%. The present invention limits the mass percentage of Mg to the above range, and can be combined with other alloy elements to form a nano-precipitated phase, which can improve the strength of the aluminum alloy.
[0026] In terms of mass percentage, the aluminum alloy powder provided by the present invention includes 0.6% to 0.8% Ti, preferably 0.65% to 0.75%; as an embodiment of the present invention, the mass percentage of Ti can be 0.62%, 0.66%, 0.69%, 0.71%, 0.73% or 0.77%. The present invention limits the mass percentage of Ti to the above range. When additive manufacturing is performed, a metastable D0 is formed under the action of Ti. 22 -Al3Ti phase can serve as an effective heterogeneous nucleation core and promote the formation of equiaxed crystals, which is beneficial to grain refinement and improving the crack resistance of aluminum alloys; and Ti can form intermetallic compounds with other alloying elements, which is beneficial to improving the wear resistance of aluminum alloys.
[0027] In terms of mass percentage, the aluminum alloy powder provided by the present invention includes 1-2% Mn, preferably 1.2-1.8%; as an embodiment of the present invention, the mass percentage of Mn can be 1.1%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7% or 1.9%. The present invention limits the mass percentage of Mn to the above range. During additive manufacturing, Mn is supersaturated and solid-dissolved in the aluminum matrix, which increases lattice distortion, improves work hardening ability and oxidation resistance, and is beneficial to improving the wear resistance of the aluminum alloy.
[0028] In terms of mass percentage, the aluminum alloy powder provided by the present invention includes a balance of Al.
[0029] In the present invention, the particle size of the aluminum alloy powder is preferably 10 to 100 μm, more preferably 15 to 55 μm. As an embodiment of the present invention, the aluminum alloy powder can be a combination of different particle sizes, wherein the mass of the particle size less than 15 μm accounts for 10%, the mass of the particle size between 15 and 55 μm accounts for 80%, and the mass of the particle size greater than 55 μm accounts for 10%. The present invention limits the particle size of the aluminum alloy powder to the above range, which can take into account both the forming performance and the economy.
[0030] The present invention adds Si, Mn and Ti elements to the Al-Cu-Mg alloy. When additive manufacturing is performed, a low melting point eutectic can be formed under the action of Si to fill the dendrite gap, thereby reducing the tendency of the alloy to crack; a metastable D0 is formed under the action of Ti.22 -Al3Ti phase can serve as an effective heterogeneous nucleation core and promote the formation of equiaxed crystals, which is beneficial to grain refinement; at the same time, Mn is supersaturated and solid-dissolved in the aluminum matrix, which increases the lattice distortion, improves the work hardening ability and oxidation resistance, which provides an aluminum alloy powder composition suitable for high-performance wear-resistant laser additive manufacturing of aluminum alloy structural parts.
[0031] The present invention also provides a method for preparing the aluminum alloy powder described in the above technical solution.
[0032] In the present invention, the aluminum alloy powder is prepared by a gas atomization method; the present invention has no particular limitation on the specific parameters of the gas atomization method, and the parameters for preparing aluminum alloy powder by a gas atomization method well known to those skilled in the art can be used.
[0033] The present invention also provides the use of the aluminum alloy powder described in the above technical solution in laser additive manufacturing.
[0034] The present invention also provides a method for preparing aluminum alloy by laser additive manufacturing, using the aluminum alloy powder described in the above technical solution and adopting a selective laser melting process for additive manufacturing.
[0035] In the present invention, the laser power of the selective laser melting process is preferably 300-350 W, more preferably 320-330 W; as an embodiment of the present invention, the laser power of the selective laser melting process may be 305 W, 315 W, 325 W, 335 W, 340 W or 345 W. The laser power affects the sintering temperature, and the laser power within the above range is conducive to the rapid melting of the aluminum alloy powder.
[0036] In the present invention, the scanning speed of the selective laser melting process is preferably 1000-1500 mm / s, more preferably 1200-1300 mm / s; as an embodiment of the present invention, the scanning speed of the selective laser melting process can be 1050 mm / s, 1150 mm / s, 1250 mm / s, 1350 mm / s or 1450 mm / s. When the scanning speed is within the above range, both material quality and processing efficiency can be taken into account.
[0037] In the present invention, the scanning line spacing of the selective laser melting process is preferably 80 to 120 μm, more preferably 90 to 110 μm. As an embodiment of the present invention, the scanning line spacing of the selective laser melting process may be 85 μm, 95 μm, 100 μm, 105 μm or 115 μm. When the scanning line spacing is within the above range, both material quality and processing efficiency can be taken into account.
[0038] In the present invention, the preheating temperature of the substrate during the additive manufacturing is preferably 70-100° C., more preferably 80-90° C.; as an embodiment of the present invention, the preheating temperature of the substrate may be 75° C., 80° C., 85° C., 90° C. or 95° C. By preheating the substrate, the temperature gradient during laser scanning can be reduced, which is beneficial to reducing the risk of material cracks.
[0039] In the present invention, the layer thickness during additive manufacturing is preferably 20-40 μm, more preferably 25-35 μm; as an embodiment of the present invention, the layer thickness during additive manufacturing can be 22 μm, 24 μm, 27 μm, 32 μm or 38 μm. The layer thickness within the above range is conducive to improving the density and forming quality of the material.
[0040] The present invention has no special requirements for other operations of the additive manufacturing, and conventional operations in the art may be used.
[0041] The present invention also provides a laser additive manufacturing aluminum alloy prepared by the preparation method described in the above technical solution.
[0042] In the present invention, the phase composition of the laser additively manufactured aluminum alloy includes an aluminum matrix and an intermetallic compound, and the intermetallic compound preferably includes AlMnSi, AlMgSi and AlTi. The intermetallic compound is formed in situ during the additive manufacturing process, has a composite reinforcement effect, and significantly improves the wear resistance of the aluminum alloy; the element dosage and printing parameters can also be adjusted as needed to obtain different combinations of intermetallic compounds, enriching the product composition of the aluminum alloy.
[0043] As an embodiment of the present invention, the density of the laser additively manufactured aluminum alloy is preferably higher than 99%. High density means that the alloy has fewer pores, which is beneficial to improving the mechanical properties and crack resistance of the alloy. As an embodiment of the present invention, the density is tested using the Archimedes method.
[0044] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] The invention discloses an aluminum alloy powder suitable for laser additive manufacturing, wherein the specific composition is as follows (wt.%): Cu 4.4%, Mg 1.8%, Si 2.4%, Mn 1.5%, Ti 0.7%, Fe≤0.2%, Zn≤0.1%, and the rest is Al.
[0047] The aluminum alloy powder is prepared by a gas atomization method, and is vibrated and sieved to obtain aluminum alloy powder with a particle size of 80% between 15 and 53 μm and a powder morphology mainly showing a uniform spherical shape, which is used for additive manufacturing.
[0048] The aluminum alloy powder was observed using a scanning electron microscope to obtain a SEM image, such as Figure 1 As shown. Figure 1 It can be seen that the morphology of aluminum alloy powder is mainly spherical.
[0049] Application Example 1
[0050] The aluminum alloy powder obtained in Example 1 was processed by selective laser melting (LPBF), and the parameters of LPBF were: laser power: 320 W; scanning speed: 1200 mm / s; scanning line spacing: 100 μm; layer thickness: 30 μm; before LPBF forming, the aluminum alloy powder was dried in a vacuum drying oven at 120°C for 4 h.
[0051] The processed aluminum alloy is recorded as Al-Cu-Mg-Si-Mn-Ti aluminum alloy. The actual photo is as follows Figure 2 shown.
[0052] The density of the processed aluminum alloy is 99.5% according to the Archimedes method test.
[0053] The microstructure of the Al-Cu-Mg-Si-Mn-Ti aluminum alloy formed in Example 1 was observed using a metallographic microscope, a transmission electron microscope, and a scanning electron microscope. Figure 3 As shown, (a) is a metallographic micrograph, (b) is a TEM image, and (c) and (d) are SEM images. From (a), it can be seen that the strip-like structure is arranged along the printing direction, without defects such as cracks and pores; from (b), it can be seen that the equiaxed crystals and columnar crystals are evenly distributed in the microstructure of the Al-Cu-Mg-Si-Mn-Ti aluminum alloy (indicated by arrows); from (c) and (d), it can be seen that there are fine and evenly distributed precipitates in the microstructure of the Al-Cu-Mg-Si-Mn-Ti aluminum alloy (indicated by arrows), and the precipitates are intermetallic compounds, mainly Al2Cu(Mg), Mg2Si; the nano-precipitates are mainly D0 22 -Al3Ti.
[0054] Comparative Example 1
[0055] An aluminum alloy powder has the following specific components (wt.%): Cu 4.3%, Mg 3.16%, Si 1.96%, Fe≤0.2%, Zn≤0.1%, and the rest is Al.
[0056] The aluminum alloy powder is prepared by a gas atomization method, and is vibrated and sieved to obtain aluminum alloy powder with a particle size range of 24 to 65 μm and a powder morphology mainly showing a uniform spherical shape, which is used for additive manufacturing.
[0057] The obtained aluminum alloy powder was processed by selective laser melting (LPBF) process. The parameters of LPBF were: laser power: 340 W; scanning speed: 1000 mm / s; scanning line spacing: 100 μm; layer thickness: 30 μm; before LPBF forming, the aluminum alloy powder was dried in a vacuum drying oven at 120°C for 4 hours.
[0058] The processed aluminum alloy is recorded as Al-Cu-Mg-Si aluminum alloy. The density of the processed aluminum alloy is 99.0%.
[0059] Comparative Example 2
[0060] An aluminum alloy powder has the following specific components (wt.%): Cu 4.2%, Mg 3.04%, Si 2.10%, Ti 0.67%, Fe≤0.2%, Zn≤0.1%, and the rest is Al.
[0061] The aluminum alloy powder is prepared by a gas atomization method, and is vibrated and sieved to obtain aluminum alloy powder with a particle size range of 24 to 65 μm and a powder morphology mainly showing a uniform spherical shape, which is used for additive manufacturing.
[0062] The obtained aluminum alloy powder was processed by selective laser melting (LPBF) process. The parameters of LPBF were: laser power: 280 W; scanning speed: 1000 mm / s; scanning line spacing: 100 μm; layer thickness: 30 μm; before LPBF forming, the aluminum alloy powder was dried in a vacuum drying oven at 120°C for 4 hours.
[0063] The processed aluminum alloy is recorded as Al-Cu-Mg-Si-Ti aluminum alloy. The density of the processed aluminum alloy is 99.3%.
[0064] Comparative Example 3
[0065] The aluminum alloy formed by the comparative example 2 was further subjected to aging treatment at a temperature of 190° C. for 5 h.
[0066] The processed aluminum alloy is recorded as AgedAl-Cu-Mg-Si-Ti aluminum alloy. The density of the processed aluminum alloy is 99.3%.
[0067] Test Example 1
[0068] Friction coefficient measurements were performed using a ball-on-disc friction tester.
[0069] The sample size is 10×10×3mm3 , the contact material is hard steel ball (diameter 6mm, HRC 60).
[0070] The friction test adopts dry friction conditions, the ambient temperature is room temperature (about 25° C.), and the relative humidity is 40% to 60%.
[0071] Test standard: The test is based on ASTM G99 standard (used to evaluate the friction and wear properties of materials).
[0072] The sliding speed was 10 mm / s, and the friction test load was set to three working conditions: 2.1 N, 10 N, and 24 N. Each test lasted 30 minutes and was repeated 3 times.
[0073] Data collection: Real-time recording of the change curve of friction coefficient over time.
[0074] Application Example 1 The friction coefficient variation curve of the processed aluminum alloy is as follows Figure 4 As shown, from Figure 4 It can be seen that the friction coefficient gradually decreases with the increase of load, which proves that the aluminum alloy processed and formed by the present invention has excellent friction reduction and wear resistance under high load.
[0075] After the test is completed, the curve is smoothed to extract the steady-state friction coefficient. The wear rate (W) is calculated according to the following formula:
[0076]
[0077] in:
[0078] ΔV: Material wear volume, in mm 3 ;
[0079] F: applied load, in N;
[0080] d: sliding distance, in meters.
[0081] The wear volume is calculated by measuring the wear scar cross section using laser scanning or profilometry (ISO 20808).
[0082] The wear rates of the aluminum alloys processed in Application Example 1 and Comparative Examples 1 to 3 are recorded in Table 1.
[0083] Table 1 Wear rate record of aluminum alloys processed by application examples and comparative examples
[0084]
[0085]
[0086] According to the data in Table 1, draw a bar graph, such as Figure 5 As shown. Figure 5 It can be seen from the data in Table 1 that the present invention significantly improves the wear resistance of the aluminum alloy by adding Si, Ti and Mn to the Al-Cu-Mg alloy.
[0087] It can be seen from the above embodiments and comparative examples that the aluminum alloy powder provided by the present invention has no cracks and pores during laser additive manufacturing; during laser additive manufacturing, intermetallic compounds can be formed, which significantly improves the wear resistance of the aluminum alloy.
[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An aluminum alloy powder suitable for laser additive manufacturing, wherein the composition of the aluminum alloy powder comprises, by mass percentage, 3-5% Cu, 1-3% Si, 1-2% Mg, 0.6-0.8% Ti, 1-2% Mn, and the balance Al.
2. The aluminum alloy powder according to claim 1, characterized in that: In terms of mass percentage, the aluminum alloy powder comprises 3.5-4.5% Cu, 1.5-2.5% Si, 1.2-1.8% Mg, 0.65-0.75% Ti, 1.2-1.8% Mn, and the balance Al.
3. The aluminum alloy powder according to claim 1 or 2, characterized in that: The particle size of the aluminum alloy powder is 10 to 100 μm.
4. The method for preparing the aluminum alloy powder according to any one of claims 1 to 3, characterized in that: The aluminum alloy powder is prepared by gas atomization method.
5. Use of the aluminum alloy powder according to any one of claims 1 to 3 or the aluminum alloy powder prepared by the preparation method according to claim 4 in laser additive manufacturing.
6. A method for preparing aluminum alloy by laser additive manufacturing, characterized in that: The aluminum alloy powder according to any one of claims 1 to 3 or the aluminum alloy powder prepared by the preparation method according to claim 4 is additively manufactured using a selective laser melting process.
7. The preparation method according to claim 6, characterized in that: The parameters of the selective laser melting process include: laser power of 300-350W, scanning speed of 1000-1500mm / s, and scanning line spacing of 80-120μm.
8. The preparation method according to claim 6, characterized in that: The preheating temperature of the substrate during the additive manufacturing is 70-100°C.
9. The preparation method according to claim 6, characterized in that: The layer thickness during the additive manufacturing is 20 to 40 μm.
10. The laser additive manufacturing aluminum alloy prepared by the preparation method according to any one of claims 6 to 9, characterized in that: The phase composition of the laser additively manufactured aluminum alloy includes an aluminum matrix and an intermetallic compound.